Incidence of transient ischemic attack in Auckland, New Zealand, in 2011 to 2012. - Barber, P; Krishnamurthi, R; Parag, V; Anderson, N; Ranta, A; Kilfoyle, D; Wong, E; Green, G; Arroll, B; Bennett, D; Witt, E; Rush, E; et al. (American Heart Association, 2016)
Background and Purpose There have been few recent population-based studies reporting the incidence (first ever) and attack rates (incident and recurrent) of transient ischemic attack (TIA). Methods The fourth Auckland Regional Community Stroke study (ARCOS IV) used multiple overlapping case ascertainment methods to identify all hospitalized and nonhospitalized cases of TIA that occurred in people ≥16 years of age usually resident in Auckland (population ≥16 years of age is 1.12 million), during the 12 months from March 1, 2011. All first-ever and recurrent new TIAs (any new TIA 28 days after the index event) during the study period were recorded. Results There were 785 people with TIA (402 [51.2%] women, mean [SD] age 71.5 [13.8] years); 614 (78%) of European origin, 84 (11%) Māori/Pacific, and 75 (10%) Asian/Other. The annual incidence of TIA was 40 (95% confidence interval, 36–43), and attack rate was 63 (95% confidence interval, 59–68), per 100 000 people, age standardized to the World Health Organization world population. Approximately two thirds of people were known to be hypertensive or were being treated with blood pressure–lowering agents, half were taking antiplatelet agents and just under half were taking lipid-lowering therapy before the index TIA. Two hundred ten (27%) people were known to have atrial fibrillation at the time of the TIA, of whom only 61 (29%) were taking anticoagulant therapy, suggesting a failure to identify or treat atrial fibrillation. Conclusions This study describes the burden of TIA in an era of aggressive primary and secondary vascular risk factor management. Education programs for medical practitioners and patients around the identification and management of atrial fibrillation are required.